Demand For Domestic Tourism: Market From Kuching, Sarawak - Norazirah, Ayob; Salbiah, Edman (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Domestic tourism would help to facilitate maximum capacity of the international tourism. Thus, main objective of this paper is to understand Malaysian community’s attitude and behavior towards the domestic tourism. It is important to comprehend what they consider important in making choice decisions one alternative over another, consequently the conception might be very useful especially in designing and implementing effective marketing programs. In addition, this study also described the components of domestic tourism in Malaysia, its volume, value and profile, and mapping its characteristics as a functional basis for domestic tourism’s planning and management. Collectively, the residents of Kuching, Sarawak have positive attitude towards traveling and having holiday domestically. 87.2% were found engaged in domestic tourism with at least one holiday trip in 2004. Average number of trips made by domestic tourists from Kuching within the boundary of Malaysia in year of 2004 was 2.94 trips.